The Invasion of the South Army Air Force Operations, and the Invasion of Northern and Central Sumatra - Remmelink, Willem (Leiden University Press, 2021)
Between 1966 and 1980, the War History Office of the National Defense College of Japan (now the Center for Military History of the National Institute for Defense Studies) published the 102-volume Senshi Sōsho (War History Series). The present book completes the trilogy of English translations of the sections in the Senshi Sōsho series on the Japanese operations against the former Dutch East Indies (Indonesia). The first volume (The Invasion of the Dutch East Indies, 2015) details the army operations, the second volume (The Operations of the Navy in the Dutch East Indies and the Bay of Bengal, 2018) the navy operations, and this third volume the army air force operations. The three volumes provide an unparalleled insight into the Japanese campaign to capture Southeast Asia and the oil fields in the Indonesian archipelago in what was at that time the largest transoceanic landing operation in the military history of the world. It was also the first time in history that air power was employed with devastating effect over such enormous distances, posing complex technical and logistical problems.